PENERAPAN METODE INKUIRI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATA PELAJARAN IPA SISWA KELAS IV SD NEGERI 2 METRO BARAT TAHUN AJARAN 2010/2011 - Sumaryatun Sumaryatun (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
Obstacles in the process of learning science in the fourth grade of SD Negeri 2 Metro West is caused because the learning activities have only centered on teachers to be dominated by the tendency of a lecture and assignments, so that students are not actively involved. The problem of this thesis is "What is the use of inquiry method can improve student motivation and learning outcomes science subjects fourth grade 2 Metro West State School Year 2010/2011?" The purpose of this is to determine empirically increased motivation to follow the teaching and learning process and student learning outcomes in science subjects fourth grade 2 Metro West State School Year 2010/2011. This research is a classroom action research in which there are two cycles. Collecting data in this social inquiry learning strategy is test result of learning, observation and documentation sheet. Achievement test used to determine the increase motivation to follow the students' learning process. Documentation sheets used to collect data such as the history of the study site and others. From the results of this study showed an increased motivation and learning outcomes of students of fourth grade science subjects S 2 Metro West State School Year 2010/2011, it can be seen from the average increase student motivation and learning outcomes of the first cycle of 18.38% and in cycle II to be 21.24%. In this case means an increase learning outcomes of the first cycle and the second cycle by 2.86% increased student learning outcomes is evidence that the inquiry method can increase student motivation and learning outcomes of fourth grade science subjects S 2 Metro West State School Year 2010/2011. Keywords: Activities and outcomes of learning, inquiry